Ascher Syndrome: A Case Report - Sunil S Mishra; Anita D Munde; Sneha S Tambe; Anjum Ara J. Farooqui (Wolters Kluwer Medknow Publications, 2020)
The Ascher or Laffe-Ascher syndrome is characterized by blepharochalasis, double lip and nontoxic thyroid enlargement. The syndrome is a rare manifestation and often remains undiagnosed. We report a case of Ascher syndrome in a 16 years old boy with double lip including upper and lower lip, blepharochalasis and an additional finding of mild clinodactyly which makes it a rare presentation. The article describes in brief an overview of the syndrome.